2013
DOI: 10.1158/1535-7163.mct-12-1028
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Platinum Resistance in Preclinical Models of Ovarian Cancer Using the Neddylation Inhibitor MLN4924

Abstract: The nearly ubiquitous development of chemoresistant disease remains a major obstacle against improving outcomes for ovarian cancer patients. In this investigation we evaluated the preclinical activity of MLN4924, an investigational inhibitor of the NEDD8-activating enzyme, in ovarian cancer cells. Efficacy of MLN4924 both alone and in combination with platinum was assessed. Overall, single agent MLN4924 exhibited moderate activity in ovarian cancer cell lines. However, the combination of MLN4924 with cisplatin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 23 publications
4
56
1
Order By: Relevance
“…An increasing number of studies have demonstrated that MLN4924 promotes a DNA damage response, cell cycle arrest, apoptosis and senescence in a number of cancer cell types (8,(11)(12)(13)15,22,23). In accordance with these previous studies, the current study observed that MLN4924 promotes apoptosis and the DDR in PTX-resistant NSCLC cells.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…An increasing number of studies have demonstrated that MLN4924 promotes a DNA damage response, cell cycle arrest, apoptosis and senescence in a number of cancer cell types (8,(11)(12)(13)15,22,23). In accordance with these previous studies, the current study observed that MLN4924 promotes apoptosis and the DDR in PTX-resistant NSCLC cells.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, MLN4924 exhibits potent antitumor activity in numerous types of cancer (14). Notably, previous studies have indicated that MLN4924 overcomes platinum resistance in preclinical models of ovarian cancer (15,16), suggesting that inhibiting neddylation with MLN4924 may be a novel strategy to target drug resistance in cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of cell cycle regulatory proteins upon MLN4924 treatment was constantly accompanied with DNA damage response, which was partially responsible for the apoptosis and senescence induced upon NEDDylation inhibition (Soucy et al 2009a, b;Mackintosh et al 2013;Jia et al 2011a, b). Given the potency and the unique mechanism of MLN4924 in inducing DNA damage in cancer cells, synergistic interactions between MLN4924 with other DNA-damage-inducing compounds (platinum, cytarabine, Cisplatin, mitomycin C) and radiation will promote its incorporation into current treatment regimens for human malignancies (Nawrocki et al 2013(Nawrocki et al , 2015Yang et al 2012;Wei et al 2012;Kee et al 2012;Jazaeri et al 2013;Garcia et al 2014). These studies highlighted potential incorporation of MLN4924 into current treatment regimens as addition of MLN4924 was shown to sensitize malignant cells to those traditional therapeutic strategies.…”
Section: Skp2mentioning
confidence: 99%
“…11,26). Finally, the discovery that treatment of cancer cells with the neddylation inhibitor pevonedistat (also known as MLN4924) inhibits cancer cell lines and tumors and is associated with significant induction of rereplication demonstrated that rereplication can be induced pharmacologically, and this may have an anticancer activity (27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%